2020
DOI: 10.1111/tri.13689
|View full text |Cite
|
Sign up to set email alerts
|

Nail changes in upper extremity allotransplantation: onychomadesis as the presenting sign of allograft rejection – a retrospective study

Abstract: Upper extremity allotransplantation (UEA) is the more common type of vascularized composite allotransplantation of which more than 80 patients have benefited worldwide. These allografts includealong with the skinthe nail unit, a specialized epithelial appendage which may be the target of graft rejection. We report an UEA recipient who developed, as an initial manifestation of graft rejection, onychomadesis, that is shedding of the nail plate starting from the proximal nail bed. On this occasion, we reviewed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The majority of onychomadesis cases also improved, while exacerbation of symptoms, residual sequelae, or recurrence were reported in 0.8%, 2.4%, and 3.2% of studies, respectively. One study reported that 3 out of 44 patients with recurrent onychomadesis treated with 40% urea cream worsened ( 3 ), and 3 studies reported residual sequelae, such as onycholysis, thin and brittle nails, and minor scarring after onychomadesis ( 8 – 10 ). Studies reported recurrence of onychomadesis in the setting of idiopathic familial or sporadic cases, or in a child with spinal muscular atrophy ( 11 , 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of onychomadesis cases also improved, while exacerbation of symptoms, residual sequelae, or recurrence were reported in 0.8%, 2.4%, and 3.2% of studies, respectively. One study reported that 3 out of 44 patients with recurrent onychomadesis treated with 40% urea cream worsened ( 3 ), and 3 studies reported residual sequelae, such as onycholysis, thin and brittle nails, and minor scarring after onychomadesis ( 8 – 10 ). Studies reported recurrence of onychomadesis in the setting of idiopathic familial or sporadic cases, or in a child with spinal muscular atrophy ( 11 , 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…These changes are seen on the skin of the allograft and the sentinel skin flap often performed in cases of FA to monitor graft rejection [8,9 ▪ ,10]. Pain [10] or alopecia [13] may be the presenting signs of CR in UEA and FA, respectively, and nail changes may be seen in CR in UEA [17]. On the basis of these presentations, three clinical patterns of CR were individualized in FA, including vitiligo-like, lichen planus-like and scleroderma-like CR [12 ▪ ].…”
Section: Surrogates For the Diagnosis Of Chronic Rejection In Vascula...mentioning
confidence: 99%
“…Nail matrix transplantation surgery is technically complex with high failure rates. 1 Three-dimensional (3D) is a promising technology for nail reconstruction. 2 Three-dimensional technology has been used to generate nail units in vitro and in vivo (Table 1).…”
mentioning
confidence: 99%
“…Nail matrix transplantation surgery is technically complex with high failure rates. 1 Three-dimensional (3D) is a promising technology for nail reconstruction. 2…”
mentioning
confidence: 99%